Pengaruh metode jarimatika Pengaruh Metode Jarimatika Terhadap Kecepatan Berhitung dan Hasil Belajar Siswa Pada Materi Perkalian Kelas IV Di SD Muhammadiyah - Anisa, Mia Fitra; Taufik Saleh, Yopa; Suci Pratiwi, Anggia (Griya Journal of Mathematics Education and Application, 2024)
This research aims to determine the effect of the Jarimatics method on calculation speed and student learning outcomes in class IV multiplication material at Muhammadiyah Elementary School. This research is the experimental research. The population in this study were all fourth grade students at Muhammadiyah elementary school. The sample in this study was all class IV, totaling 11 students. The sampling technique in this research was a saturated sampling technique. Saturated sampling technique is a sampling technique where all members of the population are sampled. Based on the research results and discussion analysis, the data in this study is normally distributed and homogeneous with a significance level for data normality of 0.868 > 0.05, and a significance level for data homogeneity of 0.143 > 0.05. Hypothesis testing in this research uses the paired sample test (t-test). Based on the results of the hypothesis test, the significance value for calculating speed was obtained at 0.000 < 0.05 and the significance value for learning outcomes was 0.00 < 0.05. So it can be concluded in this study that Ho is rejected and Ha is accepted, meaning that the Jarimatics method influences the speed of calculation and student learning outcomes in class IV multiplication material at Muhammadiyah elementary school.